Analisis Sistem Kompensasi Menggunakan Metode Salary Mapping Adhered Dan Overlapping Pada UKM XYZ - Akmalia, Annisa; Athillah Adha, Cinta; Handayani, Elis; Elysia, Laili; Firsta Wandira, Syifa; Kartika, Lindawati (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This research aims to help provide recommendations and improvements in calculating wages in UKM XYZ using the overlapping method and complying with it. It is hoped that this research can provide a clear picture of the existing incentive system in SME XYZ and provide a strong basis for analyzing and designing a more effective and sustainable incentive structure for the company. The data obtained in this research was obtained from interviews and direct observation at UKM XYZ. The findings obtained in the field indicate that UKM XYZ has not carried out appropriate system improvements, therefore improvements are needed. The results obtained after improving the recovery system using the overlapping method and complying with it were that the total new salary using overlapping was IDR 72,860,000 or an increase of 3.06% compared to the original salary. Meanwhile, by using the compliant method the salary increases by 1.54%. So from these results it can be concluded that the most suitable method to justify the salary structure of SME XYZ is the overlapping method.